Illegal Medicines Circulation Through E-commerce: Consumer Legal Protection Challenges by the Food and Drug Supervisory Centre - Alfin, Fiorenzya; Muhammad, Danang Wahyu (Fakultas Hukum Universitas Islam Jakarta, 2024)
Although there are regulations regarding the provisions of drug trading, the facts show that there are still many cases of illegal drug trading, especially on e-commerce platforms. The purpose of this study is to analyse the challenges of legal protection for consumers on the circulation of illegal drugs traded through e-commerce platforms and analyse the efforts of the Food and Drug Supervisory Centre (BBPOM) in supervising the circulation of illegal drugs traded through e-commerce platforms. The research method used is normative legal research with a statutory approach. The results showed that regulations related to online drug sales are regulated in Article 12 of BPOM Regulation Number 32 of 2020 concerning Amendments to BPOM Regulation Number 8 of 2020 concerning Supervision of Drugs and Food Circulated Online and Article 4 of BPOM Head Regulation Number 24 of 2017 concerning Criteria and Procedures for Drug Registration. Legal protection of consumers in good faith is carried out through preventive efforts by conducting deterrence and monitoring through cyber patrols. While repressive efforts are carried out by providing compensation, compensation and/or replacement if in filing a civil lawsuit the business actor and marketplace are proven guilty. The supervision carried out by BBPOM is to conduct supervision before circulation as a preventive measure and supervision during circulation.